Concerto for the violin of Gyorgy Ligeti: their relevance as representative works of the late Non-Atonal style of the composer - Santos Machado Dantas, Ivan Paula [UNESP]; Lunsqui, Alexandre Roberto [UNESP] (Univ Estadual Parana, Escola Musica & Belas Artes Parana, 2015)
This paper discuss the importance of Gyorgy Ligeti's Violin Concerto, and its relevance among the composer's late style works. The main characteristics of Ligeti's music are described, from his textural music, such as Atmosphsres, to his recent Hamburg Concerto. The singularities of what Ligeti calls his non-atonal style are of special interest and are particularly discussed, such as the use of triadic formation in a non-tonal context, the simultaneous use of diverging intonation systems, the use of traditional forms like the passacaglia and hocket. Then, a more detailed analysis of the Violin Concerto allows us to establish relationships between these singularities, bringing a better and more contextual understanding of the piece that can be used in performance. Detailed analysis of each movement is presented, using an eclectic analytical approach.
Keywords: Gyorgy Ligeti; Violin Concerto; Music Analysis; Non-atonal style